PENERAPAN AKUNTANSI ASET TETAP PADA BANK NAGARI CABANG UTAMA PADANG - Helmida, Helmida; Ramayani,, Citra; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
Abstract Fixed Assets held by Bank Nagari Main Branch Padang has the shape and uses different. Provision of Fixed Assets shall be strictly in accordance with the requirements, so that the investment made on fixed assets will not be in vain and accountable. Issues that are examined in this study is the calculation and determination of Fixed Assets depreciation. This study aims to determine : 1) Implementation of Fixed Asset accounting at the Main Branch of Bank Nagari Padang, 2) Accounting treatment of fixed assets at the Main Branch of Bank Nagari Padang.This type of research in this study is descriptive . This research was conducted at the Main Branch of Bank Nagari Padang. Data were collected through library research and field research, field research conducted by interview. Then the data obtained were analyzed with descriptive analysis method.The results showed that : 1) the general Bank Nagari Padang Main Branch has implemented Financial Accounting Standards. Where expenditure is the added benefit of an asset, then the fixed assets are capitalized in accordance with the Group Assets as capital expenditure (capex ), and to determine whether capitalized or not first have to get approval from headquarters. While spending is only one component repair equipment Fixed Asset Routine without increasing the useful life of the fixed assets then the expenditure is classified as revenue expenditure (revenue expenditure) and expenditure is charged as an expense in the period expenditures undertaken. 2) Accounting Treatment in Bank Nagari Main Branch Padang in general accordance with Financial Accounting Standards. Where In assessing the Fixed Assets, Bank Nagari Padang Main Branch Historical Cost valuation method, where the purchase price at the time the transaction is used as the basis for recording the value of the fixed assets. The elements included in the purchase price consists of the purchase price of assets plus other costs (until fixed assets are ready for operation). Regarding depreciation Main Branch Bank Nagari Padang using the straight-line method (straight line method), based on the estimated useful lives of the assets. By using this method of calculation of depreciation expense each period will be the same.